Optimalisasi Jaringan Pipa Air Minum di Kota Maumere Kabupaten Sikka Nusa Tenggara Timur - Priambodo, Sebastianus; Widyawati, Intan (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2025)
Access to drinking water is needed for every resident. The National Urban Water Supply Project (NUWSP) aims to improve access to piped drinking water for urban communities. The NUWSP program in 2021 involved the central and local governments collaborating through funding to support the Wair Puan Regional Drinking Water Company (Perumda Air Minum Wair Pu'an, Sikka Regency). This program will optimize the drinking water supply system (SPAM) to achieve the target of 100% access to drinking water. In 2021, Perumda Wair Pu'an had 19,625 house connections, representing a 62.97% service level for residents. Raw water source data for 2021 showed a water consumption of 170.5 l/second, serving four service areas. The population concentration of Maumere City across service areas is uneven, necessitating SPAM optimization through additional water sources, pipe networks, and water reservoirs. Based on the results of the water balance analysis for the 10-year planning period, Perumda Wair Pu'an requires optimization of the drinking water pipe network through additional assets. The addition of assets in the form of 4,124 m of transmission pipes and 20,199 m of distribution pipes. The construction of new pump wells and reservoirs with a capacity of 600 m3 in zone 1 and a reservoir with a capacity of 200 m3 in zone 3. Optimization of the drinking water pipe network at Perumda Wair Pu'an will increase the current service level to 71.62%.